PEMBINAAN KEAGAMAAN SISWA DI PONDOK PESANTREN AL- MUTTAQIN SUNGAI AUR PASAMAN BARAT - Mahmuda, Mahmuda (State Institute for Islamic Studies Batusangkar, 2019)
This study aims to find out and analyze the students' religious formation in the Aur West Pasaman Al-Muttaqin Islamic Boarding School for the prayer activities of the fardhu in congregation, the Al-Qur'an reading activities and the Tahfiz Al-Qur'an activities. In this study the authors used a qualitative approach with a type of case study (case study). Data collection techniques in this study are observation, interview and documentation. To test the validity of the data, researchers used a source, technique and time triangulation technique. In analyzing data, researchers conducted data reduction, data appearance, drawing conclusions and verifying data. The results of this study indicate that students' religious formation has been implemented and implemented, but not yet maximized. The form of fardhu prayer formation in congregation is carried out such as teaching students how to perform prayers. Form students in several groups. Each student memorizes prayer readings. The form of coaching reading the Qur'an is to teach students good readings in accordance with makhrijul letters. Form students in several groups to listen to each other's readings. The form of guidance of Tahfiz Al-Qur'an is that students bring the Qur'an every day to school. Students may not arrive late when studying Tahfiz. Students always try to memorize the last week before entering the new memorization.